2004
DOI: 10.2165/00002018-200427050-00005
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Telmisartan in Patients with Arterial Hypertension

Abstract: The safety and efficacy of telmisartan found in controlled studies is maintained in a large postmarketing population that included sizeable patient subgroups potentially at higher risk for adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(34 citation statements)
references
References 28 publications
3
27
0
4
Order By: Relevance
“…17,18 This applies also to the high tolerability and low incidence of side effects seen in our study. The observed inverse relation between treatment effect and number of previous BP drugs used is not surprising, as many patients with BP polypharmacy in fact do have a refractory hypertension which also could apply to telmisartan.…”
Section: Discussionsupporting
confidence: 63%
“…17,18 This applies also to the high tolerability and low incidence of side effects seen in our study. The observed inverse relation between treatment effect and number of previous BP drugs used is not surprising, as many patients with BP polypharmacy in fact do have a refractory hypertension which also could apply to telmisartan.…”
Section: Discussionsupporting
confidence: 63%
“…As the general linear model approach used reduction in symptom intensity after intake of medication as dependent variable, this is not surprising as subjects with a high baseline value can reduce absolute symptom intensity to a greater extent. This phenomenon has also been observed in the analysis of databases from observational treatment studies in other indications, for instance arterial hypertension23 or overactive bladder syndrome 24…”
Section: Discussionmentioning
confidence: 53%
“…80,82 with fluid retention and weight gain. 95 The differences in adverse-effect profiles between selective PPAR␥ modulators like telmisartan and conventional PPAR␥ agonists like the thiazolidinediones could be related to the fact that SPPARMs do not stimulate PPAR␥ as much as the glitazones and also have more selective effects on the recruitment of key transcription cofactors that influence PPAR␥ target gene expression profiles. 85,96 Molecular modeling studies have suggested that telmisartan may interact with the ligand-binding domain of PPAR␥ differently than the glitazones, thereby resulting in different conformational changes in the receptor.…”
Section: Implications For Treatment Of the Metabolic Syndromementioning
confidence: 99%